Chlorogenic acid prevents vancomycin‐induced nephrotoxicity without compromising vancomycin antibacterial properties. (10th July 2020) - Qu, Shaoqi; Dai, Cunchun; Hao, Zhihui; Tang, Qihe; Wang, Haixia; Wang, Jinquan; Zhao, Hongqiong
Abstract : Vancomycin (VCM) is an effective chemotherapeutic agent commonly used against gram‐positive microorganisms but has serious nephrotoxic side effects that limit its effectiveness. New therapeutics and strategies are urgently needed to combat VCM associated nephrotoxicity. In this study, we determined the protective effect of chlorogenic acid (CA) in a rat model of VCM‐induced nephrotoxicity. VCM administration led to markedly elevated blood urea nitrogen and serum creatinine levels that could be prevented with CA co‐administration. VCM‐mediated oxidative stress was also significantly attenuated by CA as reflected by decreased malondialdehyde and nitric oxide in VCM‐treated kidneys. CA administration also prevented the VCM‐mediated decrease in the renal antioxidative enzyme activities of glutathione reductase, glutathione peroxidase, and catalase and led to increased levels of reduced glutathione that had been depleted by VCM. Moreover, CA administration clearly inhibited VCM‐induced expression of nuclear factor‐kappa B, inducible nitric oxide synthase and the downstream pro‐inflammatory mediators tumor necrosis factor‐α and interleukins 1β and 6. Apoptotic markers were also markedly down‐regulated with CA. Overall, CA treatment mitigated VCM‐induced oxidative and nitrosative stresses and countered the apoptotic and inflammatory effects of VCM. Notably, CA did not affect the antibacterial activity of VCM in vitro.